Custom, Economic Roles, and Islamic Values in Shaping The Communication Patterns of Coastal Women in Bengkulu City, Indonesia - Ledyawati Ledyawati; Lesti Heriyanti; Linda Safitra (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
This study examines how custom, economic roles, and Islamic values shape the communication patterns of coastal women in Bengkulu City, Indonesia. It argues that women’s communication in coastal communities should be understood as a socially constructed and domain-specific practice rather than merely as a gendered speaking style. Using a qualitative approach with a focused ethnography design, the study was conducted in three coastal sub-districts: Malabero, Berkas, and Sumber Jaya. Data were collected through semi-structured in-depth interviews, participant observation, and document study involving 24 women, including fish traders, fishermen’s wives, seafood processors, and members of women’s fisher groups. The data were analyzed thematically. The results indicate that Melayu Bengkulu customary norms tend to shape women’s communication as careful, indirect, and oriented toward politeness in family and community forums. Economic roles in fish trading and seafood processing create more assertive communicative spaces, particularly in markets and household economic decision-making. Islamic values operate ambivalently by reinforcing norms of adab while providing moral legitimacy for women to speak, ask questions, and share experiences in majelis taklim. This study demonstrates that the communicative agency of coastal women is contextual, negotiated, and shaped by the forms of legitimacy available across customary, economic, and religious domains.